Infiltration Wells as a Solution to Runoff and Flooding Problems in Purwodinatan Subdistrict Semarang City - Masvika, Hendra; Haikal, Bintang Husni; Purwanto, Purwanto; Firmawan, Ferry; Khasanah, Nur (Faculty of Engineering, Universitas Semarang, 2026)
During the rainy season or under heavy rainfall events, roads in Purwodinatan Subdistrict, Semarang City, frequently experience water ponding. This condition disrupts community activities and other road users. Insufficient drainage capacity to accommodate rainfall volume, along with inadequate drainage maintenance that leads to sedimentation, contributes to surface runoff and water inundation. These conditions require further mitigation measures to control surface runoff and shorten the drainage recession time. Therefore, the planning of infiltration wells is proposed as an alternative solution to address this problem. The implementation method adopted in this study consists of a literature review related to the design dimensions of infiltration wells, followed by the calculation of the Bill of Quantities (BoQ). The planning conducted represents a preliminary approach and is solely based on a literature review of infiltration well design, without involving detailed technical analyses of infiltration well capacity. Based on the BoQ calculation, a cost of IDR 6,462,954.92 is required to construct one infiltration well along the Bubakan Baru Street segment, where 9 infiltrations well locations are identified within a single road segment. The final outputs of this activity include a map of proposed infiltration well locations and the BoQ calculation to be submitted to the subdistrict authority. This activity serves as a preliminary planning stage to assist the community in estimating the dimensions, number of locations, and cost of infiltration wells.